Beyond the Hype: A Systematic Exploration of Emerging Thematic Trends and Persistent Challenges in Combating Greenwashing Across Global Supply Chains - Vivian Cherono; Md. Tota Miah; Ildikó Rudnák; Szűcs Csaba (Administrative Sciences)
This study aimed to determine how research has highlighted greenwashing in supply chains by identifying emerging themes and pinpointing gaps that must be addressed in combating greenwashing in global supply chains. Using the PRISMA framework, 58 papers published up to 2024 were critically examined. Through this review, five key emerging themes are presented: standardization of regulatory policies, technological innovations for transparency, environmental, social, and governance (ESG) criteria, the role of NGOs in monitoring greenwashing incidences, and industry-specific case studies. The study also identified a dearth of research on industry-specific cases, regional disparities, the implementation of technological innovations for supply chain transparency, and the role of supply chain stakeholders in reducing greenwashing, with only a few papers highlighting NGOs and government. We propose a conceptual framework for combating greenwashing and to promote sustainability in global supply chain operations, paving the way for further academic exploration. We also suggest solutions as well as a guide for future researchers to explore areas that are still underdeveloped and offer recommendations to supply chain policymakers on addressing greenwashing.